Disharmonization in Extending Flat Use Rights: Perumnas Management vs. Owners' Rights Implication - Rofi Wahanisa; Ismail Pratama (Penerbit Goodwood, 2026)
Purpose: Flats (rumah susun) are increasingly viewed as efficient urban housing solutions owing to limited land and rising demand. However, Indonesia's legal framework is problematic, especially for extending Building Use Rights (Hak Guna Bangunan/HGB) over common land under Perum Perumnas' management rights. This stems from the disharmony between Government Regulation (PP) No. 13/2021 on Flats Implementation and PP No. 83/2015 on Perum Perumnas, which lack clear mechanisms for HGB renewal by unit owners.Research Methodology: This study employs a normative juridical method with statutory and conceptual approaches to examine the issue. Data were gathered through library research on relevant laws and doctrines and then analyzed qualitatively using descriptive-analytical techniques to interpret regulatory conflicts.Results: The findings show that inconsistencies between housing and Perum Perumnas regulations cause legal uncertainty for flat owners' HGB sustainability over common land. Conflicts cannot be resolved solely by lex posterior derogat legi priori but must incorporate lex specialis derogat legi generali principles. Conclusions: Regulatory harmonization is crucial to ensure legal certainty, safeguard unit owners' rights, and balance Perum Perumnas' Management Rights (Hak Pengelolaan/HPL) authority with community interests in vertical housing.Limitations: As a normative study relying on library research, it lacks empirical data from field observations, stakeholder interviews, and real-case implementations.Contributions: Identifies key disharmony between PP 13/2021 and PP 83/2015; proposes harmonization via dual lex principles to secure HGB extensions over Perumnas HPL, aiding policymakers and jurisprudence on urban flats.